Abnormal Brain Network Topology During Non–rapid Eye Movement Sleep and Its Correlation With Cognitive Behavioral Abnormalities in Narcolepsy Type 1 - Zhu, Xiaoyu; Ni, Kunlin; Tan, Huiwen; Liu, Yishu; Zeng, Yin; Yu, Bing; Guo, Qiyong; Xiao, Li (Frontiers in Neurology, 2021)
Simultaneous electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) were applied to investigate the abnormalities in the topological characteristics of functional brain networks during non-rapid eye movement（NREM）sleep. And we investigated its relationship with cognitive abnormalities in patients with narcolepsy type 1 (NT1) disorder in the current study.